1982
DOI: 10.1111/j.1365-2125.1982.tb01914.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and smoking on the pharmacokinetics of pindolol and propranolol.

Abstract: 1 Pharmacokinetic investigations were carried out in a group of 32 ambulant normal male volunteers in order to determine the effect of age and smoking on steady‐state plasma levels of pindolol and propranolol. There were four groups of 8: young non‐smokers (YNS), young smokers (YS), old non‐smokers (ONS) and old smokers (OS). Each subject received, in a randomized cross‐over sequence, 5 mg pindolol and 80 mg propranolol three times daily for 2 days with an interval of at least 14 days between the two treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The clearances of sotalol, digoxin, terbutaline, clorazepate, dexamethasone, methimazole, carbamazepine, phenobarbitone, phenytoin, primidone, pancuronium, ampicillin, cefazolin, cefuroxime, cephradine, and morphine are all increased during pregnancy. 13,21-23 The elimination half-life of pindolol administered in the form of the racemic mixture to healthy volunteers ranges from 3-4 h. 17,[24][25][26] In the present study, the elimination half-lives of the pindolol isomers were slightly lower, with an approximate value of 2.9 h being obtained for both enantiomers. The elimination half-life of pindolol does not differ between pregnant and nonpregnant patients, probably since the increase in the apparent clearance of both enantiomers during pregnancy is compensated for by an increase in the apparent volume of distribution.…”
Section: Resultsmentioning
confidence: 71%
“…The clearances of sotalol, digoxin, terbutaline, clorazepate, dexamethasone, methimazole, carbamazepine, phenobarbitone, phenytoin, primidone, pancuronium, ampicillin, cefazolin, cefuroxime, cephradine, and morphine are all increased during pregnancy. 13,21-23 The elimination half-life of pindolol administered in the form of the racemic mixture to healthy volunteers ranges from 3-4 h. 17,[24][25][26] In the present study, the elimination half-lives of the pindolol isomers were slightly lower, with an approximate value of 2.9 h being obtained for both enantiomers. The elimination half-life of pindolol does not differ between pregnant and nonpregnant patients, probably since the increase in the apparent clearance of both enantiomers during pregnancy is compensated for by an increase in the apparent volume of distribution.…”
Section: Resultsmentioning
confidence: 71%
“…Like labetalol (see section 2.2.5), pindolol has been shown to decrease total peripheral resistance and will not further compromise heart rate in the patient with a low resting heart rate (Toth et a,l. The Cmax and AVC of pindolol are significantly increased in elderly patients (Hitzenberger et al: 1982) and the tl/2 is increased 50 to 90% (Frishman 1983;Gretzer et al 1986). However, 2 studies in the elderly (Allegraud 1978;Persson 1978) indicated that 57 to 61% of elderly patients needed concomitant therapy with diuretics to attain adequate antihypertensive control.…”
Section: Pindololmentioning
confidence: 99%
“…Similar observations of increased plasma o' +1 +1 concentrations of 1-adrenoceptor blockers in elderly patients as compared to younger subjects have been made for propranolol (Castleden o . X & George, 1979;Hitzenberger et al, 1982), . pindolol (Hitzenberger et al, 1982) atenolol +1 +1 (Rigby et al, 1985) and acebutolol (Roux et al, 1983).…”
Section: A°tmentioning
confidence: 99%
“…X & George, 1979;Hitzenberger et al, 1982), . pindolol (Hitzenberger et al, 1982) atenolol +1 +1 (Rigby et al, 1985) and acebutolol (Roux et al, 1983). However, other comparisons of the kinetics in young and old healthy subjects have a failed to reveal differences for propranolol (Schneider et al, 1980;Rigby et al, 1985), or°m etoprolol (Quarterman et al, 1981;Rigby et X .o * 2 al., 1985).…”
Section: A°tmentioning
confidence: 99%